2021
DOI: 10.1101/2021.04.08.439029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational clamping by a membrane ligand activates the EphA2 receptor

Abstract: The EphA2 receptor is a promising drug target for cancer treatment, since EphA2 activation can inhibit metastasis and tumor progression. It has been recently described that the TYPE7 peptide activates EphA2 using a novel mechanism that involves binding to the single transmembrane domain of the receptor. TYPE7 is a conditional transmembrane (TM) ligand, which only inserts into membranes at neutral pH in the presence of the TM region of EphA2. However, how membrane interactions can activate EphA2 is not known. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Even differences in pH can be mimicked by defining different charged states for acidic/basic groups, or by using the Titratable Martini approach (Grünewald et al, 2020). Moreover, trimers or oligomer can be accurately studied (Westerfield et al, 2021) with Martini 3 or even interactions with larger protein complexes (Liaci et al, 2021). Additional simulations and experimental studies are needed to delineate the possible effects of such variables on the TM dimer structural configurations and their stability.…”
Section: Resultsmentioning
confidence: 99%
“…Even differences in pH can be mimicked by defining different charged states for acidic/basic groups, or by using the Titratable Martini approach (Grünewald et al, 2020). Moreover, trimers or oligomer can be accurately studied (Westerfield et al, 2021) with Martini 3 or even interactions with larger protein complexes (Liaci et al, 2021). Additional simulations and experimental studies are needed to delineate the possible effects of such variables on the TM dimer structural configurations and their stability.…”
Section: Resultsmentioning
confidence: 99%
“…The transition between states occurred in a sigmoidal fashion with a midpoint (pH50) of 5.00 ± 0.01 (24). For pH-responsive peptides that bind the TM of an RTK, the presence of that RTK can increase the pH50 due to an increase in tendency to be inserted in the presence of a membrane binding partner (15,23). For this reason, we repeated the experiment using proteo-liposomes containing a peptide mimic of the TM of EGFR (TM-EGFR).…”
Section: Pet1 Is a Ph-responsive Peptide That Interacts With The Tm R...mentioning
confidence: 99%
“…Alves et al (15) evolved this concept and designed the peptide TYPE7 to be specific for the RTK EphA2. TYPE7 binds the TM to allosterically regulate EphA2 kinase activity by causing a configurational change (23). This method of regulation is likely to be more selective for EphA2 than targeting the highly conserved kinase domain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the interactions involved in TM-TM recognition inside the membrane is an important challenge. Moreover, recent studies have demonstrated how the activity of specific Ephs may be controlled by small peptides that specifically recognize their TMDs, and thereby change how the TM helices bind to one another (their configuration) [27,28]. Thus, the conserved role of TMDs in regulating the function of Eph receptors makes them promising targets for therapeutic intervention.…”
Section: The Family Of Eph Receptors Their Domain Structure and Functionmentioning
confidence: 99%
“…Similarly, the recently designed TYPE7 peptide is also highly soluble in the aqueous solution that inserts into cellular membranes at slightly acidic pH. The TM state of TYPE7 interacts with EphA2 and induces receptor oligomerization and phosphorylation [27,28]. Using CG MD simulation our laboratory has helped to suggest a mechanism by which the TYPE7 peptide stabilizes the active configuration of the helix dimer by forming a 2:1 (EphA2 TMs: peptide) trimer complex and thereby promoting EphA2 oligomerization.…”
Section: Association Of Inhibitor/activator Peptides As An Avenue To Integrate Tmd Behavior With Whole-length Eph Receptor Function: Fluomentioning
confidence: 99%